2008
DOI: 10.1080/08880010802237450
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1 ABERRATIONS IN ETV6/RUNX1-POSITIVE AND ETV6/RUNX1-NEGATIVE PATIENTS: Its Hemato-Pathological and Prognostic Significance in a Large Cohort (619 Cases) of ALL

Abstract: A large-cohort study (619) of acute lymphoblastic leukemia (ALL) revealed an ETV6/RUNX1 (previously known as TEL/AML1) incidence of 18% in pediatric B-cell precussor ALL, indicating no geographical heterogeinity. Association of CD34-negative phenotype, peak incidence in the 3- to 7-year age group, and a comparatively low frequency of ETV6 homologue loss in ETV6/RUNX1-positive cases were distinct findings in this series. Additional genetic changes, such as ETV6 loss, extra RUNX1, ETV6/RUNX1 duplication, and MLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…This finding is consistent with our previous study [27] and another cohort of 928 patients [Nahar A et al in communication]. Data from various studies from Asian countries also indicated low prevalence (13% -19%) of ETV6/RUNX1 [54]- [56].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding is consistent with our previous study [27] and another cohort of 928 patients [Nahar A et al in communication]. Data from various studies from Asian countries also indicated low prevalence (13% -19%) of ETV6/RUNX1 [54]- [56].…”
Section: Discussionsupporting
confidence: 82%
“…The peak incidence of ETV6/RUNX1 was in lower age group of 1 -10 years as reported in our previous studies as well as in studies from other Asian countries [27] [52] [55] [59]. Trisomy 21 and ETV6 allelic loss were most frequent additional abnormalities in ETV6/RUNX1 positive group, however these abnormalities were common in overall BCP-ALL patients [27] [59].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Several studies have reported deletion of the non-translocated ETV6 allele as a recurrent abnormality occurring in conjunction with ETV6/RUNX1 [6-9]. In our cohort, del(12p) was found in 14 patients (22%), but was not found to affect EFS.…”
Section: Discussionmentioning
confidence: 49%
“…[1617] We have also detected nonreciprocal BCR-ABL with 9q deletion/res ABL deletion/res BCR deletion in a large CML series of 2000 cases (our unpublished data). Our vast experience in various hematological malignancies like Acute Lymphoblastic Leukemia (ALL)[1820] in lymphoma[21] which support the notion that genomic deletions followed by translocations are common events in hematological malignancies.…”
Section: Resultsmentioning
confidence: 68%